Traditionalism and electoral politics in the land of the hornbills, Sarawak - Ghazali Mayudin; Mohd Rizal Mohd Yaakop (Penerbit UKM, 2008)
This article discusses traditionalism as an issue in electoral politics by analyzing Sarawak 2006 State Legislative Assembly Election. Traditional politics is based on communal differences and on ethnic-based framework; it focuses on the existence of ethnic divisions that constitute the basis of more traditional politics. In 2006 we saw the revival of Traditional Politics and processes which challenge traditional politics to engage a new way of looking. The results of the 2006 State Legislative Assembly Election of Sarawak were a shock to both the government and the opposition parties. The election results also showed that especially among the Malay voters, traditional politics still persist as they do not favour political change. On the other hand Chinese voters were more calculative and rational in their choice of party and candidates- more pragmatic and in favour of change. This article stresses external and internal issues raised by the Chinese-based parties, Sarawak United People’s Party (SUPP) and Democratic Action Party (DAP), in Sarawak State Elections of 2001 and 2006; and the effects on the election results. In 2001, the main campaign issue was on external issues such as the 9/11 incident and the racial conflicts in other countries. On the other hand, in 2006, domestic issues such as the increase of petroleum price, land lease and land premium were predominant.